FACTORS THAT DRIVE PRACTICE OF INCOME SMOOTHING - Alviandy, Timothy Carolus; Handojo, Irwanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Practice of income smoothing is one of four earnings management patterns. Income smoothing itself could be defined as a method used by management to reduce profit fluctuations that are deemed abnormal through various accounting methods or through transactions. This research is done to acquire empirical evidence about the effect of company size, financial leverage, profitability, public ownership, tax avoidance and cash holding towards the practice of income smoothing. The method used in sample selection is purposive sampling method. This research uses companies from consumer cyclical and consumer non-cyclical sector that is listed on the Indonesia Stock Exchange (IDX) from the year 2020 to 2022. The number of companies that fit criteria and can be used as research samples is 49 companies with 147 data samples. The result of the research shows that variables company size, profitability, public ownership, tax avoidance, and cash holding does not have any effect on income smoothing and the variable financial leverage has an effect on income smoothing.